2014
DOI: 10.1007/s00702-014-1252-9
|View full text |Cite
|
Sign up to set email alerts
|

Safety aspects of incobotulinumtoxinA high-dose therapy

Abstract: Botulinum toxin (BT) used for dystonia and spasticity is dosed according to the number of target muscles and the severity of their muscle hyperactivities. With this no other drug is used in a broader dose range than BT. The upper end of this range, however, still needs to be explored. We wanted to do this by a prospective non-interventional study comparing a randomly selected group of dystonia and spasticity patients receiving incobotulinumtoxinA (Xeomin(®)) high-dose therapy (HD group, n = 100, single dose ≥4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 13 publications
1
35
0
2
Order By: Relevance
“…However, in this series, patients were treated with fixed doses, which were somewhat lower (not exceeding 50U for blepharospasm and 120e240U for CD), than used in clinical practice. In some patients, higher doses are required when CD is complex (Dressler and Saberi, 2006). We do not have data on high doses at shorter intervals over a longer time frame.…”
Section: Blepharospasm and Hemifacial Spasmmentioning
confidence: 88%
“…However, in this series, patients were treated with fixed doses, which were somewhat lower (not exceeding 50U for blepharospasm and 120e240U for CD), than used in clinical practice. In some patients, higher doses are required when CD is complex (Dressler and Saberi, 2006). We do not have data on high doses at shorter intervals over a longer time frame.…”
Section: Blepharospasm and Hemifacial Spasmmentioning
confidence: 88%
“…Excluding other 26 articles not meeting inclusion criteria, we obtained full copies of the 16 potentially suitable reports for further assessment. After inclusion of 2 articles of interest from the reference lists of the selected articles and exclusion of other 10 articles, 8 studies met study eligibility criteria, and were finally included in the overall review [8][9][10]20,[22][23][24][25] (Tables 1 and 2). …”
Section: Methodsmentioning
confidence: 99%
“…In fact, the mean FAT score improved, but the benefit was not significant [24]. Finally, a recent study demonstrated that very high doses of incobotulinumtoxinA (minimum 400 U and maximum 1200 U) injected into fifty-four patients suffering from spasticity of several etiologies (15 suffered with hemispasticity, 13 with arm spasticity, 12 with tetraspasticity, 9 with paraspasticity, and 5 with leg spasticity) did not cause any paresis or any autonomic dysfunction distant from the target muscles which could be attributed to BoNT therapy or complete secondary therapy failure [25]. Moreover, the few side effects reported (weakness, feeling of residual urine, constipation, being bedridden, especially in tetraparesis or paraparesis, whereas blurred vision attributed to presbyopia) have been attributed to the underlying condition and not to BoNT-A action [22].…”
Section: First Author and Year Of Publicationmentioning
confidence: 96%
“…In a prospective, open-label noninterventional study, Dressler evaluated the safety outcomes in 15 suffered with hemispasticity, 13 with arm spasticity, and 5 with leg spasticity due to stroke for 90% of the patients treated up to 1200 U of incobotulinumtoxinA (dose range: 400-1200 U; mean dose ± standard deviation: 570.1 ± 158.9 U). No signs of motor or autonomic dysfunction have been reported and no patient developed Ab production and secondary treatment failure [13]. The safety of 600 U of incobotulinumtoxinA has been also tested in 11 spastic stroke survivors evaluating possible changes in autonomic heart drive.…”
Section: High Doses Of Incobotulinumtoxina For the Treatment Of Postsmentioning
confidence: 99%